Mast cells are essential in the development of exposure-associated exercise-induced bronchoconstriction in a mouse model - Marain, Nora F.; Byttebier, Fien; Colemont, Marieke; Dilissen, Ellen; Cremer, Jonathan; Bullens, Dominique MA; Dupont, Lieven J.; Vanoirbeek, Jeroen A. (Frontiers in Immunology, 2025)
BackgroundCold air and air pollution are known triggers to induce symptoms in exercise-induced bronchoconstriction (EIB). Mast cells are hypothesized to be a key player in the pathogenesis of EIB. This study aims to investigate the role of mast cells using mast cell deficient (Cpa3cre/+) mice and with mast cell stabilizers (Doxantrazole) in an exposure-associated mouse model of EIB.MethodsMale Cpa3cre/+ mice and wild type littermates or BALB/c mice were exposed to a submaximal running protocol in cold environment (4°C) or resting period (room temperature) 5 days for 3 weeks after oropharyngeal challenge with saline or 0.1 mg/ml diesel exhaust particles (DEP). BALB/c mice were intraperitoneally injected with 16.5 mg/kg Doxantrazole or placebo (0.5% NaHCO3) during the last week. Twenty-four hours after the last running or resting session, lung function, lung inflammation and immune mediated response was determined.ResultsInhibition of mast cells by Doxantrazole or mice lacking functional mast cells (Cpa3cre/+), resulted in blunting of bronchial hyperreactivity, both in acute breathing pattern and in hyperreactivity to increasing doses of methacholine. Neutrophilic inflammation was still present after Doxantrazole treatment, but not in Cpa3cre/+ mice. These results were similar in neutrophil extracellular traps and neutrophil-linked cytokines and chemokines. Macrophage activaty was also reduced in the absence of functional mast cells.ConclusionMast cells are crucial in the development of bronchial hyperreactivity and macrophage activation. Additionally, they have a complex interplay with neutrophilic inflammation. These findings highlight the potential of mast cell modulation as therapeutic strategy in exposure-associated EIB.